The functional -94 insertion/deletion ATTG polymorphism in the promoter region of NFKB1 gene increases the risk of sporadic colorectal cancer. - Mohd Suzairi, M.S.; Tan, S.C.; Ahmad Aizat, Abdul Aziz; Mohd Aminudin, Mustapha; Siti Nurfatimah, Mohd Shahpudin; Andee, Z.D.; Ankathil, Ravindran (Elsevier Science, Ltd., 2013)
Objective: To investigate the allele and genotype frequencies of NFKBI -94 ins/de! ATTG (rs28720239) polymorphism and to evaluate the association between the polymorphism and colorectal cancer (CRC) risk in Malaysian population. Methods: Genomic DNA was extracted from the peripheral blood samples of 474 study subjects, which consisted of 237 histopathologically confirmed CRC patients and an equal number of cancer-free controls. The NFKBI -94 ins/de! ATTG (rs28720239) polymorphism was genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and confirmed by DNA sequencing. The association between the polymorphic genotypes and CRC risk was evaluated by deriving odds ratios (ORs) and 95% confidence intervals (Cls) using unconditional logistic regression analysis. Results: The frequencies of wildtype (del/del), heterozygous ( del/ins) and variant (ins/ins) genotypes in CRC patients were 31.7%, 53.6% and 14.8%, respectively, while those in cancer-free controls were 35.0%, 58.2% and 6.8%, respectively. The frequency of the variant genotype was significantly higher in cases compared to controls (P < 0.01 ). Evaluation of the risk association of the polymorphic genotypes revealed that the variant genotype could contribute to a significantly increased risk of CRC (OR= 2.42, 95% CI= 1.24-4.73, P < 0.01 ). Conclusions: The variant allele of NFKBI -94 ins/de! ATTG (rs28362491) polymorphism is associated with higher risk of sporadic CRC in Malaysian population.